2022
DOI: 10.1117/1.jbo.27.1.015001
|View full text |Cite
|
Sign up to set email alerts
|

Interpretable deep learning approach for oral cancer classification using guided attention inference network

Abstract: . Significance: Convolutional neural networks (CNNs) show the potential for automated classification of different cancer lesions. However, their lack of interpretability and explainability makes CNNs less than understandable. Furthermore, CNNs may incorrectly concentrate on other areas surrounding the salient object, rather than the network’s attention focusing directly on the object to be recognized, as the network has no incentive to focus solely on the correct subjects to be detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Specific imaging method not disclosed NN based on DenseNet121 architecture, pre-trained on ImageNet Sensitivity Specificity Precision AUROC F 1 Grad-CAM Sensitivity 98.75 Specificity 100 Precision 100 AUROC 0.99 F 1 0.99 Lin et al 24 Heterogenous dataset from 4 different smartphones NN based on HRNet-W18 architecture, pre-trained on ImageNet Sensitivity Specificity Precision AUROC F 1 Grad-CAM Sensitivity 83.0 Specificity 96.6 Precision 0.84 AUROC 0.946 F 1 0.9 Welikala et al 25 Smartphone images of oral lesions as part of the MeMoSA initiative Multiple pre-trained NNs. Best performing algorithm based on VGG19 architecture Sensitivity Specificity Precision Accuracy F 1 Grad-CAM Sensitivity 85.7 Specificity 76.4 Precision 0.77 Accuracy 80.9 F 1 0.81 Figueroa et al 26 Clinical photographs. Specific imaging method not disclosed NN based on VGG19 architecture, pre-trained on ImageNet Sensitivity Specificity Accuracy Grad-CAM Sensitivity 74.4 Specificity 89.1 Accuracy 83.8 Warin et al 27 SLR camera NN based on ResNet architecture, pre-trained on ImageNet Sensitivity Specificity Precision AUROC Sensitivity 98.4 Specificity 91.7 Precision 92.0 AUROC 0.950 Tanriver et al 28 Clinical photographs taken in clinical department, supplemented by images from various search engines Multiple pre-trained NNs; best performance using EfficientNet-b4 architecture Sensitivity Precision F 1 Sensitivity 89.3 Precision 86.2 F 1 85.7 Jeyaraj et al 29 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific imaging method not disclosed NN based on DenseNet121 architecture, pre-trained on ImageNet Sensitivity Specificity Precision AUROC F 1 Grad-CAM Sensitivity 98.75 Specificity 100 Precision 100 AUROC 0.99 F 1 0.99 Lin et al 24 Heterogenous dataset from 4 different smartphones NN based on HRNet-W18 architecture, pre-trained on ImageNet Sensitivity Specificity Precision AUROC F 1 Grad-CAM Sensitivity 83.0 Specificity 96.6 Precision 0.84 AUROC 0.946 F 1 0.9 Welikala et al 25 Smartphone images of oral lesions as part of the MeMoSA initiative Multiple pre-trained NNs. Best performing algorithm based on VGG19 architecture Sensitivity Specificity Precision Accuracy F 1 Grad-CAM Sensitivity 85.7 Specificity 76.4 Precision 0.77 Accuracy 80.9 F 1 0.81 Figueroa et al 26 Clinical photographs. Specific imaging method not disclosed NN based on VGG19 architecture, pre-trained on ImageNet Sensitivity Specificity Accuracy Grad-CAM Sensitivity 74.4 Specificity 89.1 Accuracy 83.8 Warin et al 27 SLR camera NN based on ResNet architecture, pre-trained on ImageNet Sensitivity Specificity Precision AUROC Sensitivity 98.4 Specificity 91.7 Precision 92.0 AUROC 0.950 Tanriver et al 28 Clinical photographs taken in clinical department, supplemented by images from various search engines Multiple pre-trained NNs; best performance using EfficientNet-b4 architecture Sensitivity Precision F 1 Sensitivity 89.3 Precision 86.2 F 1 85.7 Jeyaraj et al 29 …”
Section: Resultsmentioning
confidence: 99%
“…S1 . Eight studies were found to have a high risk of bias across any of the 7 domains 2 , 16 , 21 , 22 , 26 , 28 , 30 , 35 . Within domain 1, 11% of studies were found to have high risk of bias, 26% low risk of bias, and 63% unclear risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figueroa et al [ 15 ] designed a DL training model which provides understandability to its prediction and guides the network to remain focused and precisely delineate the tumorous region of the image. Lim et al [ 16 ] developed a DL architecture called D'OraCa to categorize oral lesions with photographic images.…”
Section: Introductionmentioning
confidence: 99%
“…Next, compared and investigated the efficiency of regularization, convolution neural network, and transfer learning technique for classifying oral tumors. Figueroa et al [15] designed a DL training model which provides understandability to its prediction and guides the network to remain focused and precisely delineate the tumorous region of the image. Lim et al [16] developed a DL architecture called D'OraCa to categorize oral lesions with photographic images.…”
Section: Introductionmentioning
confidence: 99%